World Intellectual Property Report 2019 : the Geography of Innovation: Local Hotspots, Global Networks. - Organization, World Intellectual Property (World Intellectual Property Report., 2019)
Where exactly is innovation taking place? Relying on millions of patent and scientific publication records, the World Intellectual Property Report 2019 documents how the geography of innovation has evolved over the past few decades.